Variable resistance to zinc intoxication among Streptococcus agalactiae reveals a novel IS1381 insertion element within the zinc efflux transporter gene czcD - Varghese, Brian R.; Goh, Kelvin G. K.; Desai, Devika; Acharya, Dhruba; Chee, Collin; Sullivan, Matthew J.; Ulett, Glen C. (Frontiers in Immunology, 2023)
Streptococcus agalactiae is an important human and animal pathogen. Zinc (Zn) is an essential trace element for normal bacterial physiology but intoxicates bacteria at high concentrations. Molecular systems for Zn detoxification exist in S. agalactiae however the degree to which Zn detoxification may vary among different S. agalactiae isolates is unclear. We measured resistance to Zn intoxication in a collection of clinical isolates of S. agalactiae by comparing bacterial growth in defined conditions of Zn stress. We found significant differences in the ability of different S. agalactiae isolates to resist Zn intoxication; some strains such as 18RS21 were able to survive and grow at 3.8-fold higher levels of Zn stress compared to other reference strains such as BM110 (6.4mM vs 1.68mM Zn as inhibitory, respectively). We performed in silico analysis of the available genomes of the S. agalactiae isolates used in this study to examine the sequence of czcD, which encodes an efflux protein for Zn that supports resistance in S. agalactiae. Interestingly this revealed the presence of a mobile insertion sequence (IS) element, termed IS1381, in the 5 region of czcD in S. agalactiae strain 834, which was hyper-resistant to Zn intoxication. Interrogating a wider collection of S. agalactiae genomes revealed identical placement of IS1381 in czcD in other isolates from the clonal-complex-19 (CC19) 19 lineage. Collectively, these results show a resistance spectrum among S. agalactiae isolates enables survival of varying degrees of zinc stress, and this phenotypic variability has implications for understanding bacterial survival in metal stress.